2019
DOI: 10.1136/tobaccocontrol-2019-054951
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating smoking control policies in the e-cigarette era: a modelling study

Abstract: BackgroundIn jurisdictions in which electronic cigarettes are currently prohibited, policy makers must weigh the potentially lower risk compared with conventional cigarettes against the risk of initiation of e-cigarettes among non-smokers.MethodsWe simulated a synthetic population over a 50-year time horizon with an open cohort model using data from Singapore, a country where e-cigarettes are currently prohibited, and data from the USA, the UK and Japan. Using the smoking prevalence and the quality-adjusted li… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
25
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 20 publications
(25 citation statements)
references
References 40 publications
0
25
0
Order By: Relevance
“…8 The evidence syntheses we reviewed provided support for the ethicality and legality of this proposed law based on human rights principles, 61 and the modelling studies demonstrated substantial health benefits to the population. 55 59 60 Consistent with the findings of the NZ simulation modelling, which demonstrated that this policy would be insufficient to achieve the country's endgame goal, 60 the proposed law will be introduced as part of a comprehensive plan that also addresses adults who currently smoke. 8 Ending commercial tobacco sales has also been implemented in Bhutan (although recently reversed) 83 and two local government areas in the USA (Beverly Hills and Manhattan Beach).…”
Section: Reviewmentioning
confidence: 71%
See 2 more Smart Citations
“…8 The evidence syntheses we reviewed provided support for the ethicality and legality of this proposed law based on human rights principles, 61 and the modelling studies demonstrated substantial health benefits to the population. 55 59 60 Consistent with the findings of the NZ simulation modelling, which demonstrated that this policy would be insufficient to achieve the country's endgame goal, 60 the proposed law will be introduced as part of a comprehensive plan that also addresses adults who currently smoke. 8 Ending commercial tobacco sales has also been implemented in Bhutan (although recently reversed) 83 and two local government areas in the USA (Beverly Hills and Manhattan Beach).…”
Section: Reviewmentioning
confidence: 71%
“…Five syntheses, including three simulation modelling studies predicting the impacts of e-cigarette use,53–55 and two narrative reviews focusing on e-cigarettes,34 56 concluded that these products have the potential to substantially reduce combustible tobacco use, and thus potentially achieve a tobacco endgame 34 53–56. Three syntheses also summarised evidence on the harms of reduced risk products, all concluding that they are less harmful than combustible tobacco 56–58.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Countries with taxes on e-cigarettes include Italy, Latvia, Portugal, Republic of Korea, Togo, and the United Kingdom 111 . Asian countries that have banned e-cigarettes include Singapore and Thailand, and Japan has banned the use of nicotine-containing e-cigarettes but not e-cigarettes without nicotine 116 . Vaping products are also prohibited in the United Arab Emirates 116 .…”
Section: Resultsmentioning
confidence: 99%
“…Asian countries that have banned e-cigarettes include Singapore and Thailand, and Japan has banned the use of nicotine-containing e-cigarettes but not e-cigarettes without nicotine 116 . Vaping products are also prohibited in the United Arab Emirates 116 . Switzerland had banned the sale of vaping products until 2018, but now they are available on the market 117 .…”
Section: Resultsmentioning
confidence: 99%